Regulating freedom of information in Malaysia / Mohamad Hisyamuddin Ghazali ... [et al.] - Ghazali, Mohamad Hisyamuddin; Adzhar, Adzrul Syafiq; Hashim, Muhammad Haziq; Zahari, Nur Syamimi (Faculty of Law, 2013)
This research is on the freedom of information law and its structure which already exists in the selected countries as well as the freedom of information enactment in the State of Selangor. The goal is to show that Malaysia needs a new set of law to regulate this right for freedom of information. This research is done by examining the current law available in Malaysia particularly in the State of Selangor. Besides that, this research seek to analyse the law and the structures of the freedom of information act in other countries such as the Freedom of Information Act 2000 applied in United Kingdom (UK) and the Promotion of The Information Act in South Africa including scholars articles, and relevant books and journals review. Upon understanding of the current situation, it becomes clear that Malaysia is in need of a set of law for regulating freedom of information to promote an open government which is visible to the people without secrecy. Thus, this research highlights the necessities for imposing law on freedom of information in shaping a better nation of Malaysia.